Inferior Vena Cava Filters: When to Place and When to Remove - Moriarty, John M.; Steinberger, Jonathan D.; Bansal, Anshuman K. (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary embolism (PE) is a common and feared result of deep vein thrombosis. While anticoagulation is the mainstay of management, interruption of flow of thrombus from leg veins to the pulmonary circulation is frequently desired either in lieu of or in addition to anticoagulation. Inferior vena cava filters have become frequently used to prevent PE despite a paucity of evidence for efficacy and increasing concerns about the long-term complications of indwelling filters.
Keywords: IVC filter; optional; retrieval; deep venous thrombosis; pulmonary embolism